Bioclimatic typology of Jujuy Province (Argentina) - Entrocassi, Gabriela S.; Hormigo, Dante F.; Gavilán, Rosario G.; Sánchez-Mata, Daniel (Lazaroa, 2014)
We report for the first time the Bioclimatic Typology of Jujuy Province (Argentina) as a result of the characterization performed following the methodology of the Bioclimatic Classification of Earth. Temperature and precipitation climatic parameters were used and annual and seasonal bioclimatic indices were also calculated. From them we determined the bioclimatic units and three bioclimatic maps were developed. The results show that the Province of Jujuy falls within the Tropical Macrobioclimate, regardless of the height above sea level at any location; and also present two types of bioclimates: Tropical Xeric and Tropical Pluviseasonal. In the region of the Puna and the Eastern Cordillera (Eastern Andes mountain range),above 2500 m asl, dominates the Tropical Xeric bioclimate, and the supra-, oro- and cryorotropical belts with dry to semiarid ombrotypes, although there are some high and cold places with Tropical subhumid Pluviseasonal bioclimate. The region ofthe lower valleys and Sierras Subandinas has Tropical Pluviseasonal bioclimate with thermo-, meso- and supratropical thermotypes and humid and subhumid ombrotypes, while the warmer valleys located at the threshold to the Chaco Plain mainly show a dry Tropical Xeric bioclimate. This research properly reflects reciprocity between climate and the distribution of existing vegetation at the province level. On the other hand, it will provide valuable information that may be used in future research and applied projects planning, management and conservation of natural resources of this wide territory.